A case report of a pathology in the ‘whip’ of a flagellicaudatan sauropod - Tom T.P. van der Linden; D. Ray Wilhite; Gunnar T. Bivens; D. Cary Woodruff; Rick J. Hunter; Tim Stecko; Brian D. Curtice (The Science of Nature, 2026)
Flagellicaudatan sauropods are well known for their elongated tails which end in a ‘whiplash’-like structure, consisting of biconvex rod-like caudal vertebrae lacking a neural arch. A remarkably well-preserved and relatively complete specimen of Barosaurus from the Upper Jurassic Morrison Formation preserves a number of these vertebrae, including the last two that terminate the axial series. The penultimate element preserves a distinct callus which we investigated, together with the terminal caudal vertebra, using X-ray computed tomography. A transverse fracture initiated the formation of the callus, highlighted by extensive, disorganized vascularization of the bone outside of the cortex. Healing was likely still ongoing as the vertebra remains in two parts. Although various etiologies can be proposed for the trauma, none can be unambiguously put forward as the cause. The last caudal shows an interesting vascular pattern, and together with the lack of a posterior articular surface, can here be definitely identified as the last vertebra in the axial series. There is substantial variability in the morphology of the last caudal vertebra throughout Sauropoda, and future studies should focus on the soft tissues in this part of the tail, thereby enlightening the potential function of the ‘whip’. We also highlight here the use of high-resolution scanning to reveal the internal structures of fossils in detail when consumptive analysis is not possible.